1988
DOI: 10.1016/0306-4530(88)90043-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory influence of oxytocin infusion on contingent negative variation and some memory tasks in normal men

Abstract: A double-blind study combining electrophysiological and psychometrical approaches was carried out to investigate the central effects of an intravenous oxytocin (OT) infusion in normal men. Contingent negative variation (CNV) was selected as the measure of central cognitive evoked potential, and the psychometric tests measured mood, vigilance and memory. OT infusion induced a significant decrease of CNV amplitude and an increase of post-imperative positive potentials in vertex derivations. A similar effect was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Biological mothers' peripheral oxytocin levels have been linked with the activation of areas of the brain involved in the dopaminergic reward system (the ventral striatum and the nucleus accumbens; Atzil, Hendler, & Feldman, ; (Strathearn et al., ) and the oxytocin‐associated hypothalamic and pituitary regions (Strathearn et al., ) when presented with stimuli involving their own infant. Although the exact mechanism linking central and peripheral activity is not known, several additional studies involving humans and animals have shown associations between peripheral oxytocin activity and central nervous system activity (Carson et al., ; Geenen, Adam, Baro, Mantanus, & Ansseau, ).…”
Section: Oxytocin and Nonhuman Mammal Maternal Carementioning
confidence: 99%
See 1 more Smart Citation
“…Biological mothers' peripheral oxytocin levels have been linked with the activation of areas of the brain involved in the dopaminergic reward system (the ventral striatum and the nucleus accumbens; Atzil, Hendler, & Feldman, ; (Strathearn et al., ) and the oxytocin‐associated hypothalamic and pituitary regions (Strathearn et al., ) when presented with stimuli involving their own infant. Although the exact mechanism linking central and peripheral activity is not known, several additional studies involving humans and animals have shown associations between peripheral oxytocin activity and central nervous system activity (Carson et al., ; Geenen, Adam, Baro, Mantanus, & Ansseau, ).…”
Section: Oxytocin and Nonhuman Mammal Maternal Carementioning
confidence: 99%
“…One activated area is the locus coeruleus, which is also considered to be a source of the P3 component among humans (Aston‐Jones & Cohen, ; Carson et al., ; Tribollet, Dubois‐Dauphin, Dreifuss, Barberis, & Jard, ). Second, there is evidence among humans that peripheral oxytocin levels are associated with ERP responses to the presentation of visual stimuli (Geenen et al., ). Taking the findings from prior research together, we hypothesized that foster mothers' oxytocin production would be positively associated with their P3 amplitudes in response to viewing infant images in the current study.…”
Section: Oxytocin and Nonhuman Mammal Maternal Carementioning
confidence: 99%
“…Oxytocin has been implicated in learning and memory processes, 59,60 but whereas the effects of oxytocin on memory have been investigated very actively in animals, research in humans remains relatively limited. [61][62][63][64][65][66] The small number of studies that were carried out showed inconsistent findings, possibly due to the variety of the experimental methods, including memory testing, stimulus material, and dose, route, and timing of oxytocin administration. 67 It is interesting to note that Heinrichs and colleagues 61 argue that there are gender-specific differences in the effect of oxytocin in reproduction-related memory.…”
Section: Reduction Of Fear Responsementioning
confidence: 99%
“…The neuromodulator oxytocin has been implicated in mediating a wide variety of social behaviors, including the facilitation of social bonds, trust, and affiliative behavior (Bartz et al , 2011; Carter, 2013; Feifel, 2012; Feldman, 2012; Guastella et al , 2013; Harris and Carter, 2013; Heinrichs and Domes, 2008; Hollander et al , 2007; Meyer-Lindenberg et al , 2011; Neumann, 2008; Stallen et al , 2012; Young and Wang, 2004). Moreover, Oxytocin has been found to affect both immediate and long-term reactions to information from a social source (Bartz et al , 2011; Bruins et al , 1992; Carter, 2013; Feldman, 2012; Geenen et al , 1988; Guastella et al , 2013; Harris and Carter, 2013; Neumann, 2008; Rimmele et al , 2009). Recent animal studies suggest that oxytocin may even exercise opposite influences in these two circumstances (Bales et al , 2013; Huang et al , 2013).…”
Section: Introductionmentioning
confidence: 99%